Konsep Self Healing bagi Mental Perspektif Hadis Nabi: Studi Tematik dengan Pendekatan Psikologi - Anita Agustina (Gunung Djati Conference Series, 2023)
This research is motivated by the development of the times which resulted in a phenomenon of a society where they are easily affected by spiritual emptiness and mental disorders. The purpose of this study is to explain the concept of self-healing for the mental in the perspective of the Prophet's hadith. This type of research uses qualitative and thematic methods, takhrij, and syarah with a psychological approach. The results and discussion in this study indicate that the concept of mental self-healing has been exemplified by the Prophet in his hadith such as the prayer contained in the book of Sunan Abi Daud hadith Number 1319, then with dhikrullah (remembrance of Allah) in the book Sahih Muslim hadith Number 2700, and by reading The Qur'an is contained in the book of Sunan Abi Daud Hadith Number 1455. This study concludes that the self-healing concept of the Prophet contained in the hadith can be a treatment solution for mentally disturbed people. This study recommends that when people are facing problems, they should apply self-healing as exemplified by the Prophet Muhammad, then for hadith reviewers with other scientific approaches that will open a wider understanding of this topic.